The THE IMPLEMENTATION OF THE MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) INTERNSHIP PROGRAM IN SOCIOLOGY STUDY PROGRAM, FACULTY OF SOCIAL SCIENCES, STATE UNIVERSITY OF JAKARTA - Kurniawati, Atik; Fitri, Meila Riskia; S. K, Marista Christina; Saputra, Dicky; Firdaus, Revania (LPPM Universitas Negeri Jakarta, 2023)
This study aims to evaluate the implementation of the independent internship program organized by the Ministry of Education, Culture, Research and Technology within the Sociology Study Program, Faculty of Social Sciences, State University of Jakarta using the CIPP evaluation model. The CIPP evaluation model focuses on 4 aspects, namely Context, Input, Process, Product. The type of approach used is a descriptive qualitative approach with data collection techniques through observation, interviews, and literature studies. The results of this study show that based on: (1) Context evaluation is still not optimal, because the involvement of Sociology students only ranges from 15% of batches 1-4 and in batch 4, especially the class of 2020, there are only 4 students who pass the Independent Internship program. Then the vision, mission, and objectives of the Sociology study program are considered to be in accordance with the objectives of the implementation of the Independent Internship program. (2) Input evaluation has been going well, due to the availability of human resources, facilities, and budget funds that are well met. Preparation for the implementation of the Independent Internship has also been well prepared by the Sociology study program and the company, and has had good quality human resources and are competent in their fields. (3) The evaluation process has run well, because it is supported by the study program and participants also have a high level of satisfaction with the Independent Internship program, both from experience, mentors, nor work. Then the effectiveness of excellent mentor assistance makes participants have no significant obstacles in the registration process until the internship program ends. (4) Product evaluation has also been carried out well, because this Independent Internship program can significantly improve the abilities and skills of participants. In addition, participants gain direct work experience and are actively involved in the company, so that participants get professional relationships and clear career paths.